#TITLE_ALTERNATIVE# - HELMI HAMDANI (NIM 13202055); Pembimbing : Dr. Ir. Suwarno, MUHAMMAD
Bushing is one of the key factors from transformer. Bushing was designed to isolatted any conductor that comes from the transformer so it's isolated from the tank and other parts of the transformer. Bushing should be well maintained and condition checked. With the bushing is well checked, the cost design and the cost calculation of the bushing's changes can be done. This can be used as a starting point to give priority to all the problems that occurs in the power system. The parameter to show the condition of the bushing is the bushing's dissipation factor (tan δ ). Tan δ indicates the amount of the power loss in the dielectric. The greater the tan δ shows the greater the amount of the power loss in the dielectric, meaning the lower quality of the isolation. The calculation of the bushing tan δ value is by using the UST (Underground Speciment Test) method. The normal value limit of tan δ is standarized by the C57.19.00 IEEE Standard General Requirements and Test Procedures for Power Apparatus Bushings and the C57.19.01 IEEE Standard Performance Characteristics and Dimensions for Outdoor Appartus Bushings. Identifying the value of tan δ, the condition of the bushings can be well observed. This final report focuses on the corelation factors that gave an effect to the value of the tan δ bushings. The factors are the longer operations (operation time) of the bushing and the load current that flows through the bushings. The result of this observation shows that the value of the tan δ bushing is effectted by the operation time and the load current. The longer the operation time and the higher the load current, make the greater the value of the tan δ.